Analisis Kesulitan Membaca pada Peserta Didik dalam Materi Teks Informasi - Yusiana Yusiana; Suhendra Suhendra; Fitri Anjaswuri (STKIP Andi Matappa Pangkep, 2023)
This case study qualitative approach research aims to find out the problems that cause reading difficulties and how to overcome reading difficulties experienced by students. The subject of this research is one of the fifth grade students of SDN Tegallangkap 01. The results show that students' reading difficulties are caused by a lack of motivation from the immediate environment, especially the parents of students who do not guide students in the learning process at home. In addition, students experience delays in reading, which should be when the age of students is worthy of learning to read but these students have not learned to read so when students reach their present age students are not yet good at reading and in class V, students can only recognize letters. Students with reading difficulties have normal vision and hearing, when reading students have difficulty spelling, connecting words, let alone reading fast. The way to deal with students who have difficulty reading is by monitoring students regularly, teachers and parents. Doing additional learning on Saturdays, especially studying in the reading category and giving more writing assignments to students because if students write a lot, automatically students will read a lot.